2018
DOI: 10.1055/a-0751-2698
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early and delayed EUS-guided drainage of pancreatic fluid collection

Abstract: Background and study aims  While endoscopic ultrasound (EUS)-guided drainage of pancreatic fluid collection (PFC) is recommended to be performed ≥ 4 weeks after onset of acute pancreatitis (AP), early (< 4 weeks) interventions are needed in some symptomatic cases. Despite feasibility of early percutaneous drainage, there have been few studies about early EUS-guided drainage of PFC. Patients and methods  Consecutive patients who received EUS-guided drainage (EUS-PCD) of infected or symptomatic PFC at the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 18 publications
(23 reference statements)
1
48
0
Order By: Relevance
“…Few studies have attempted to the role of ETD in managing PNC during early phase of illness and found that it is technically feasible with satisfactory efficacy and acceptable complication rates. [ 19 20 21 22 ] Finally, although studies have demonstrated benefits of ETD over PCD in the form of lower rates of EPF, reintervention rates, rates of surgery, and shorter hospital stay, such a comparison has not been made during early phase of illness. [ 37 38 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have attempted to the role of ETD in managing PNC during early phase of illness and found that it is technically feasible with satisfactory efficacy and acceptable complication rates. [ 19 20 21 22 ] Finally, although studies have demonstrated benefits of ETD over PCD in the form of lower rates of EPF, reintervention rates, rates of surgery, and shorter hospital stay, such a comparison has not been made during early phase of illness. [ 37 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…(both reported a median time of 23 days). [ 20 21 ] Despite high percentage of solid debris in these collections, nearly two-third of the patients could be managed by multiple double-pigtail transmural plastic stents rather than BFMS. However, merely a single-stage procedure was not sufficient and nearly half of the patients required multiple sessions of DEN prior to improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many cases, the indication for drainage occurs earlier and percutaneous intervention is generally recommended in such situations [ 5 ]. On the other hand, in cases where a lesion is located in the central area of the retroperitoneal region, it is much easier to approach by endoscopy, so endoscopic drainage might be performed after the encapsulation is confirmed [ 25 ].…”
Section: Endoscopic Drainagementioning
confidence: 99%
“…The median time for early drainage in these retrospective studies was 19 to 23 days after the onset of acute pancreatitis [ 26 ]. Complications such as perforation or bleeding did not significantly increase in patients who received early drainage [ 25 ].…”
Section: Endoscopic Drainagementioning
confidence: 99%